Sofrimento moral em trabalhadores de enfermagem do serviço de hemato-oncologia - Fruet, Isolina Maria Alberto (2016)
The daily work in nursing is often permeated by ethical and moral conflicts and dilemmas which favor the moral suffering development for its workers in different contexts of performance. This can be present specifically in hematooncology services for the particularities of that sector. Due to those situations, one looks for answering the following research question: What is the frequency and severity of moral distress experienced by nursing workers of a hemato-oncology service? Thus, the current study has as general objective to investigate the frequency and intensity of the moral suffering lived by nursing workers of hemato oncology service, andas specific objectives: to validate the instrument Moral Distress Scale Adapted in a sample of nursing workers of hematooncology of a university hospital; analyze the psychometric characteristics of Moral Distress Scale Adapted; identify the frequency and intensity of the moral suffering experienced by nursing workers according to their professional category; and, verify associations between moral distress, and socio-demographic and labor variables of nursing workers of hematooncology. It is a type of transversal research that was accomplished in a Hematooncology Service at a federal public hospital in the state of Rio Grande do Sul with 56 nursing workers using Moral Distress ScaleAdapted (MDS Brazilian version). The analysis of the data occurred through factorial analysis, descriptive statistics, and bivariate analysis. The ethical precepts of research were respected in accordance to Resolution 466/12. The results are presented in the form of two papers: the first article entitled Validation of Moral Distress Scale Adapted in Hematooncology Nursing Workers ; and the second one Moral Distressof the Workers of Nursing in the Hematooncology Service . In the former article, one presents the data of the factorial analysis, detaching the factors Lack of Competency in the Work Team, Negation of the Role of Patient s Advocate, and Disrespect for the Patient s Autonomy, with Cronbach s alpha varying from 0.86 to 0.98, being constituted in an appropriate instrument for moral suffering evaluation in that population. In the latter paper, one presents means and medians of intensity (3.27 and 3.71 respectively) and frequency (1.72 and 1.62 respectively) of the general moral suffering in the studied sample, detaching significant relationship with time of work in the section, education, professional category, team dialogue presence, knowledge about ethical committee and permanent education in the institution. It is concluded that the tool used for measuring the Moral Distress was suitable for thepopulation in question, and, since the nurses show moderate moral suffering, it is suggested the team follow-up with meetings in order to discuss subjects related to the work environment.